Management of peritoneal dialysis patients under the regular prevention and control of COVID-19 (新型冠状病毒肺炎疫情防控常态化下腹膜透析患者的管理) - ZHAO Xin (赵欣); LIU Yuting (刘宇婷); LI Hongxian (李红仙) (中西医结合护理)
Under the regular prevention and control of COVID-19, a set of interventions such as systematic prevention and control of COVID-19, home-based care, comprehensive follow-up management had been carried out to ensure the safety and quality of life of patients undergoing peritoneal dialysis. (新型冠状病毒肺炎疫情防控常态化下, 中国人民解放军海军特色医学中心腹膜透析室针对腹膜透析患者开展系列防控举措、居家护理指导、随访综合防控管理等, 保证了腹膜透析患者的生活质量及安全。)